Draft Annual Plan 1978-79 Volume-I Government of Gujrat - Planning Commission (Planning Commission, 1977)
A Draft of Gujarat’s Fifth Plan envisaging an outlay of Rs. 1053 crores was published in November, 1973. However, its finalisation was held up as in the case of the Country’s Fifth Plan in view of the serious challenges to national economy in the form of inflationary pressures, and the consequences of this phenomenon which equally affected Gujarat. As directed by the Planning Commission, the proposals for the finalisation of the Fifth Plan were forwarded to them in July, 1976. the plans for the first two years 1974-76 had been already implemented and the Plan for the year 1976-77 was already approved. Hence the finalisation of the Fifth Plan in effect meant only the updating of outlays and targets for the two year 1977-79.
General Administration Department (Planning), Government of Gujrat